Ketamine-induced bladder dysfunction is associated with extracellular matrix accumulation and impairment of calcium signaling in a mouse model - Shen, Cheng-Huang (Mol Med Rep, 2019)
Due to the rising abuse of ketamine usage in recent years, ketamine-induced urinary tract syndrome has received increasing attention. The present study aimed to investigate the molecular mechanism underlying ketamine-associated cystitis in a mouse model. Female C57BL/6 mice were randomly divided into two groups: One group was treated with ketamine (100 mg/kg/day of ketamine for 20 weeks), whereas, the control group was treated with saline solution. In each group, micturition frequency and urine volume were examined to assess urinary voiding functions. Mouse bladders were extracted and samples were examined for pathological and morphological alterations using hematoxylin and eosin staining, Masson's trichrome staining and scanning electron microscopy. A cDNA microarray was conducted to investigate the differentially expressed genes following treatment with ketamine. The results suggested that bladder hyperactivity increased in the mice treated with ketamine. Furthermore, treatment with ketamine resulted in a smooth apical epithelial surface, subepithelial vascular congestion and lymphoplasmacytic aggregation. Microarray analysis identified a number of genes involved in extracellular matrix accumulation, which is associated with connective tissue fibrosis progression, and in calcium signaling regulation, that was associated with urinary bladder smooth muscle contraction. Collectively, the present results suggested that these differentially expressed genes may serve critical roles in ketamine-induced alterations of micturition patterns and urothelial pathogenesis. Furthermore, the present findings may provide a theoretical basis for the development of effective therapies to treat ketamine-induced urinary tract syndrome.